2012
DOI: 10.3834/uij.1944-5784.2012.02.06
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors Associated with Overactive Bladder

Abstract: Introduction:The pathophysiology and management of overactive bladder (OAB) has been the subject of intensive research, but the prevalence of OAB in the community has not been well documented. This study aims to determine the prevalence of OAB among men and women attending the Universiti Kebangsaan Malaysia Medical Centre (UKMMC). This study also shows the impact of OAB on daily life activities and associated risk factors.Methods: Four hundred respondents, aged between 18 to 70 years and visiting UKMMC, were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The significant risk factors of UI among older women within general population include increasing age, pre-existing medical conditions, impaired cognition and decline in physical function [4, 6]. Older adults dealing with UI are prone to skin infections, sexual dysfunction, loss of self-esteem, dependency, depression, frailty, institutionalisation, increased caregiver burden and economic cost [4, 7–9].…”
Section: Introductionmentioning
confidence: 99%
“…The significant risk factors of UI among older women within general population include increasing age, pre-existing medical conditions, impaired cognition and decline in physical function [4, 6]. Older adults dealing with UI are prone to skin infections, sexual dysfunction, loss of self-esteem, dependency, depression, frailty, institutionalisation, increased caregiver burden and economic cost [4, 7–9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported numerous factors for the incidence or exacerbation of UI, including aging [ 11 , 15 17 ], female gender [ 16 18 ], childbirth [ 11 , 19 , 20 ], obesity [ 18 , 19 , 21 , 22 ], chronic diseases [ 17 , 18 , 23 , 24 ], menopause [ 25 , 26 ], polypharmacy [ 17 , 27 , 28 ] and movement limitations [ 17 , 18 , 25 ].…”
Section: Introductionmentioning
confidence: 99%